The therapeutic mechanism of Curcumae Radix against primary dysmenorrea based on 5-HTR/Ca2+/MAPK and fatty acids metabolomics - Yuwen Qin; Wei Zhang; Wei Zhang; Wei Zhang; Zhenhua Bian; Zhenhua Bian; Chenghao Fei; Lianlin Su; Rong Xue; Qian Zhang; Yu Li; Peng Chen; et al. (Frontiers Media S.A., 2023)
Background:Curcumae Radix (CW) is traditionally used to treat primary dysmenorrea (PD). However, the mechanisms of action of CW in the treatment of PD have not yet been comprehensively resolved.Objective: To investigate the therapeutic effects of CW on PD and its possible mechanisms of action.Methods: An isolated uterine spastic contraction model induced by oxytocin was constructed in an in vitro pharmacodynamic assay. An animal model of PD induced by combined estradiol benzoate and adrenaline hydrochloride-assisted stimulation was established. After oral administration of CW, a histopathological examination was performed and biochemical factor levels were measured to evaluate the therapeutic effect of CW on PD. The chemical compositions of the drug-containing serum and its metabolites were analyzed by ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry. Network pharmacology and serum untargeted metabolomics were used to predict the mechanism of CW treatment for PD, and the predicted results were validated by RT-qPCR, WB, and targeted fatty acid (FA) metabolism.Results:In vitro, CW can relax an isolated uterus by reducing uterine motility. In vivo, the results showed that CW attenuated histopathological damage in the uterus and regulated PGF2α, PGE2, β-EP, 5-HT, and Ca2+ levels in PD rats. A total of 66 compounds and their metabolites were identified in the drug-containing serum, and the metabolic pathways of these components mainly included hydrogenation and oxidation. Mechanistic studies showed that CW downregulated the expression of key genes in the 5-HTR/Ca2+/MAPK pathway, such as 5-HTR2A, IP3R, PKC, cALM, and ERK. Similarly, CW downregulated the expression of key proteins in the 5-HTR/Ca2+/MAPK pathway, such as p-ERK/ERK. Indirectly, it ameliorates the abnormal FA metabolism downstream of this signaling pathway in PD rats, especially the metabolism of arachidonic acid (AA).Conclusion: The development of PD may be associated with the inhibition of the 5-HTR/Ca2+/MAPK signaling pathway and FA metabolic pathways, providing a basis for the subsequent exploitation of CW.